2009
DOI: 10.1111/j.1600-051x.2009.01420.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal wound healing/regeneration following implantation of recombinant human growth/differentiation factor‐5 (rhGDF‐5) in an absorbable collagen sponge carrier into one‐wall intrabony defects in dogs: a dose‐range study

Abstract: Surgical implantation of rhGDF-5/ACS may be used safely to support periodontal wound healing/regeneration in intrabony periodontal defects without complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 54 publications
4
53
0
9
Order By: Relevance
“…Application of rhGDF-5/β-TCP however, resulted in greater, although statistically not significant, probing depth reduction and clinical attachment gain compared to the control. These findings are in agreement with those reported in previous preclinical studies indicating a beneficial effect of GDF-5 on periodontal wound healing/regeneration [10,11,19]. On the other hand, the magnitude of clinical improvements appeared to be in the range of those obtained with other regenerative materials such as a recombinant plateletderived growth factor (rhPDGF BB) on a β-TCP carrier, an enamel matrix protein derivative alone or guided tissue regeneration either alone or combined with grafting materials [20][21][22][23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Application of rhGDF-5/β-TCP however, resulted in greater, although statistically not significant, probing depth reduction and clinical attachment gain compared to the control. These findings are in agreement with those reported in previous preclinical studies indicating a beneficial effect of GDF-5 on periodontal wound healing/regeneration [10,11,19]. On the other hand, the magnitude of clinical improvements appeared to be in the range of those obtained with other regenerative materials such as a recombinant plateletderived growth factor (rhPDGF BB) on a β-TCP carrier, an enamel matrix protein derivative alone or guided tissue regeneration either alone or combined with grafting materials [20][21][22][23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, rhGDF-5 may provide an environment conducive to periodontal wound healing/regeneration affecting extracellular matrix metabolism [8]. Still other studies have shown significant periodontal regeneration in discriminating large animal models following surgical implantation of both GDF-5 and GDF-7 [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The histologic sections were photographed and digitized with a light microscope ♪ (Olympus BX50, Optical Co. LTD, Japan) coupled to a digital camera ♪♪ (C5060WZ, Sony Electronic Inc., Tokyo, Japan), at a lens magnification of ×25 that's connected to a monitor and a personal computer, using the crest of the alveolar bone and the root notch as reference points [13] (Figure 2). The histometric parameters were: -Linear measurements were performed after verification of anatomical landmarks at high magnification, and by outlining the borders of the various structures with a mouse cursor.…”
Section: For Histometric Analysismentioning
confidence: 99%
“…Finn et al [20] Évaluation Concernant les 7 études précliniques, il y avait six modèles canins [22,25,[32][33][34][35] et un modèle chez le primate [36]. Six études concernaient l'utilisation d'éponges de collagène implantées seules ou en association avec des facteurs de croissance dans la régénération de défauts osseux créés chirurgicalement [25,[32][33][34][35][36]. Dans trois études, la régénération alvéolaire était évaluée en fonction de différentes concentrations de rhBMP-2 [34], de BMP6 [33], ou de rhGDF5 [32], avec une éponge de collagène comme vecteur.…”
Section: Utilisation Des éPonges De Collagène Pour La Régénération Osunclassified
“…Six études concernaient l'utilisation d'éponges de collagène implantées seules ou en association avec des facteurs de croissance dans la régénération de défauts osseux créés chirurgicalement [25,[32][33][34][35][36]. Dans trois études, la régénération alvéolaire était évaluée en fonction de différentes concentrations de rhBMP-2 [34], de BMP6 [33], ou de rhGDF5 [32], avec une éponge de collagène comme vecteur. Dans chacune de ces trois études, l'éponge de collagène seule servait de contrôle.…”
Section: Utilisation Des éPonges De Collagène Pour La Régénération Osunclassified